FREQUENCY OF UNDIAGNOSED CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN PATIENTS WITH CORONARY ARTERY DISEASE - ullah, Raza; Salam, Shahid; Ghaffar, Tahir; Muhammad, Rahim; Khan, Imran (Journal of Ayub Medical College Abbottabad, 2017)
Background: Chronic obstructive airway disease (COPD) is considered as risk factor for coronary artery disease (CAD) along with other risk factors. This study was conducted to determine the frequency of undiagnosed chronic obstructive pulmonary disease in patients with coronary artery disease. Methods: This cross-sectional study was conducted in the Pulmonology and Cardiology wards/OPD's of Khyber Teaching Hospital Peshawar. Patients more than 35 years of age, diagnosed with CAD of either gender were included. Patients already diagnosed with COPD, recent myocardial infarction (within 7 days), left ventricular impairment, pneumothorax, bronchiectasis, comatose patient, asthmatic and those with chest trauma were excluded. All the patients underwent spirometry examination before and after administration of salbutamol (5 mg for 5 minutes) via nebulizer. FEV1/FVC less than 70% confirmed the presence of COPD. Results: Out of 151 patients, 57 (37.7%) were found to have COPD. Among them, 39 (68.42%) were male and 18 (31.57%) were female. Among male patients with COPD, 82.05% (n=32) were smokers and 17.94% (n=7) were nonsmokers while in females with COPD no one was smoker. Conclusion: COPD is an under-diagnosed progressive disease in patients with high risk patients with coronary artery disease. Keywords: Chronic Obstructive Airway Disease; Coronary Artery Disease